Penerapan Manajemen Risiko Berbasis ISO 31000 pada UMKM Aksesori Handmade: Studi Kasus Sindiayu.id - Aulia Silvana; Haura Nurul Ilmi; Naura Rahadhatul Aisy; Tariza Mega Pratiwi Garini; Alfiana (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
This study aims to systematically assess the application of risk management in accordance with the international standard ISO 31000:2018 within the Micro, Small, and Medium Enterprise (MSME) Sindiayu.id, a brand specializing in the production of handmade accessories in Bandung City. The implementation of a structured risk management process is essential in the creative sector, which is naturally vulnerable to rapid market changes, dynamic product trend evolution, and various operational fragilities. The research employed a mixed-methods approach (qualitative and quantitative) by executing four primary stages of the ISO 31000 process, where data were collected through a combination of structured online surveys (Google Forms) for the quantitative evaluation of likelihood and impact, and in-depth asynchronous online interviews (WhatsApp chat) to gain qualitative context from the decision-makers. Through the 5x5 Matrix analysis of a total of 35 risk items grouped into five main categories, the research results indicate a concentration of threats at the highest level. Specifically, five priority risks were identified at the Very High Level (score 16), encompassing systemic risks such as disruption in raw material supply (Production) and Lack of Emergency Reserve Funds (Finance), as well as intense market pressures from price competition and dependency on sales platforms (Marketing). Additionally, internal risks such as Exhaustion due to Heavy Workload also emerged as a significant threat to business continuity. The application of ISO 31000 principles facilitated the development of targeted mitigation strategies, such as supply chain diversification, strengthening operational procedures, and the legal protection of Intellectual Property Rights (IPR) through official registration. In conclusion, this research presents a specific case study on handmade accessory MSMEs, demonstrating that the establishment of a structured mitigation strategy can reinforce business governance and substantially enhance Sindiayu.id's strategic resilience in a competitive market environment (ISO, 2018; Purnomo & Handayani, 2023).